Tunneling through trademarks - Kim, Sojung; Kim, Woochan (Journal of Corporate Finance, 2022)
This study documents how trademarks can be used to benefit controlling families at the expense of outside minority shareholders. Using a sample of Korean business group firms from 2017 to 2020, we find evidence to support this. First, firms are more likely to be licensor firms if the family holds higher cash flow rights. Second, we find that the association between a firm's sales and the likelihood of it being a licensee firm (or the amount of trademark royalty payments) gets stronger when the family's cash flow rights in the firm fall further below those in the licensor firm (i.e., higher cash flow rights differentials). Third, we find that the negative association between a firm's trademark royalty payments and shareholder distribution (i.e., dividend payouts and stock repurchases) gets stronger when family's cash flow rights differentials widen. Fourth, we find that the share prices of licensee firms react negatively on the day when the full disclosure of trademark royalty payments became mandatory, and that this tendency is stronger in firms with higher trademark royalty payments and higher cash flow rights differentials. Finally, these results manifest more significantly in pure holding company groups, where alternative tunneling channels are limited.